2019
DOI: 10.14738/assrj.610.7133
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Teachers’ Readiness In Developing Science Concept Assessment Through Inquiry-Based Learning Process In Elementary Schools

Abstract: Teachers need to develop their professionalism in teaching to achieve 21st century learning competencies. The role of the teacher is not only to provide information but also to assess the learning process and outcomes comprehensively and in an integrated manner. This study aimed to describe the factors that support the readiness of teachers to carry out assessments in inquiry-based science in elementary schools. Respondents in this study were 87 elementary school teachers who were 87 students spread across fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…Moreover, to introduce their lessons and to make sure learners understood the activities, they often used a question and answer method. The outcome of this study is similar to related empirical studies by Ramnarain and Hlatswayo (2018), Kang and Keinonen (2018), Suárez et al (2018), McGrath andHughes (2018), Chi et al (2018), Wilmes and Siry (2018), Kotuľáková (2019), Uiterwijk-Luijk et al (2019), Herranen and Aksela (2019), Budiastra et al (2019), Jerrim et al (2020), Tan et al (2020), Yang et al (2020). Ramnarain and Hlatswayo (2018) revealed that teachers are less inclined to the implementation of inquiry-based learning in their lessons due to some implementation challenges.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, to introduce their lessons and to make sure learners understood the activities, they often used a question and answer method. The outcome of this study is similar to related empirical studies by Ramnarain and Hlatswayo (2018), Kang and Keinonen (2018), Suárez et al (2018), McGrath andHughes (2018), Chi et al (2018), Wilmes and Siry (2018), Kotuľáková (2019), Uiterwijk-Luijk et al (2019), Herranen and Aksela (2019), Budiastra et al (2019), Jerrim et al (2020), Tan et al (2020), Yang et al (2020). Ramnarain and Hlatswayo (2018) revealed that teachers are less inclined to the implementation of inquiry-based learning in their lessons due to some implementation challenges.…”
Section: Discussionsupporting
confidence: 88%
“…For science learning through inquiry teaching at the foundation phase teachers play important roles (Herranen & Aksela, 2019). Teachers' sufficient ability to develop lesson plans, working groups and peer support are determining factors to the readiness of teachers to adopt an inquiry-based science learning process in the foundation phase (Budiastra et al, 2019). Teachers' frequent usage of inquiry-based instruction enhances learners' performance in science examinations (Jerrim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Budiastra, Erlina & Wicaksono (2019a) reported that there are still large numbers of unqualified teachers who teach science at schools. The above statement is supported by the study findings which revealed that teachers participated in the study acquire different teaching qualifications and none of them majored in Natural Science (NS).…”
Section: Discussionmentioning
confidence: 99%
“…Budiastra, Wicaksono & Erlina (2020) indicated that teachers are supporting factors for a good education and quality of education cannot exceed the quality of a teacher. However, Budiastra, Erlina & Wicaksono (2019a) shows that there are still large numbers of unqualified teachers who teach science at schools. This means that lack of science teachers is a reality that exists in many schools.…”
Section: Literature Review Availability Of Well-trained Qualified Science Teachersmentioning
confidence: 99%
“…Teachers are supporting factors for a good education. However, the initial evaluation indicated that the number of professional teachers is still low (Budiastra, Erlina & Wicaksono, 2019a). This might be influenced by the education of prospective teachers, where prospective teachers were not yet ready to attend teacher education due to their doubts about teaching careers (Jatmiko et al 2018).…”
Section: Introductionmentioning
confidence: 99%